Physical Conditions, Psychosocial, and Social Support Affects the Quality of Life in Breast Cancer Survivors - Widodo, Dyah; Djuwadi, Ganif; Budianto, Bachtiar; Halis, Farida (Indonesian Journal of Cancer, 2025)
Background: Cancer has become one of the leading causes of death in the world. The research aims to investigate the relationship between physical condition, psychosocial and social support, and quality of life in breast cancer survivors. Method: The sample of this study was breast cancer patients who attended medical therapy at four hospitals in Malang City, including Regional General Hospital Dr. Saiful Anwar, Lavalette Hospital, Panti Waluya Hospital, and Dr. Soepraoen Military Hospital. Samples were taken using a purposive sampling technique from March to November 2022.Result: Breast cancer survivors have a good overall quality of life, as proven by an average score of 80.94. 158 respondents were included in the research for correlation analysis. The findings also revealed a correlation between physical problems (p = 0.003), psychosocial disorders (p 0.001), and social support (p = 0.01) and breast cancer survivors’ quality of life.Conclusion: The breast cancer survivors have a good quality of life. Physical problems, psychosocial disorders, and social support are related to the quality of life of breast cancer survivors. Other factors may affect the quality of life of breast cancer patients in addition to the three main factors mentioned